IMPLEMENTASI TOOLS NETWORK MAPPER PADA LOKAL AREA NETWORK (LAN) - Ginta, Prama Wira; Kusuma, Galih Putra; Negara, Edi Kusuma (Jurnal Media Infotama, 2013)
The development of computer technology in today's rapidly increasing, a lot of aspects in the world of computers that can be developed starting from the hardware ( hardware ) , software ( software ) as well as its operating system . Almost every year , every month , even every week offering computer world discoveries and developments both hardware ( hardware ) and software (the software) . The development of software on the network world is something that is very encouraging for network users , a wide range of specialized software for a network marketed by the manufacturer of the software , but of development - these developments there is the other side that we do not want, which exploit program development , as this can be detrimental to network users , we can imagine how disappointed we are , when we are indulge in the network and find out the data - we lost important data , or classified documents we are known by people who are not responsible , users exploit program is known as hackers , Tools Network Mapper is one of the many programs exploit in the world. Tools Network Mapper program called the exploit because it can be used to identify in and explores the data without the knowledge of the target computer or computer without the user's permission on the go , therefore we should be more careful - be active in the network. we already know that in order to solve a problem properly we must first study the problem itself, from the emergence of the problem until the cause and effect that caused by the problem itself , as well as in the manufacture of network security software , of course, the software maker first study one or a few programs - programs that exploit exists. In connection with our society is still relatively ignorant about the exploit in the writing program faculty research , the writer will discuss about the workings of one of the programs that exploit Tools Network Mapper in identifying in and explores the target computer data. Keywords : Application Network Mapper , Network Local Area Network